2017
DOI: 10.11648/j.jdmp.20170301.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ethanol Psidium Guava leaf extract on KCl Induced Contracted Aortic tissues of Guinea Pigs

Abstract: Hypertension is elevation of systolic blood pressure greater than or equal to 140 mm Hg and/or diastolic blood pressure greater than or equal to 90 mm Hg. It affects 1 billion people and accounts for approximately 7.1 million deaths annually. It is significant risk factor for cardiovascular disorders. Some medicinal plants are traditionally used to treat hypertension. Psidium guava is one of widely cultivated medicinal plant used as traditional medication for diabetes, vomiting, diarrhea and dyslipidemia. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(22 reference statements)
0
1
0
3
Order By: Relevance
“…Mishra et al, (Mishra et al, 2010), reported that Albizzia lebbeck bark have anti-asthmatic, anti-anaphylactic properties and pods have analgesic, anxiolytic, antiinflammatory, anti-diarrheal activities and antispermatogenic effect Sheyin et al, 2015). The Psidium guajava broadly studied for antimicrobial (Mendez et al, 2016), against diabetes (Joseph et al, 2016), anti-inflammatory (El-Ahmady et al, 2013), anti-tumor, anti-cancer (Ashraf et al, 2016), for diabetes, vomiting, diarrhea and dyslipidemias (Elias et al, 2017) and leaves aqueous extracts of Psidium guajava use for obesity and dyslipidemias (Simao et al, 2017). These outcomes ratify high UV and RFC index of above stated medicinal plants in district Faisalabad.…”
Section: Use Value (Uv) and Relative Frequency Of Citation (Rfc)mentioning
confidence: 94%
“…Mishra et al, (Mishra et al, 2010), reported that Albizzia lebbeck bark have anti-asthmatic, anti-anaphylactic properties and pods have analgesic, anxiolytic, antiinflammatory, anti-diarrheal activities and antispermatogenic effect Sheyin et al, 2015). The Psidium guajava broadly studied for antimicrobial (Mendez et al, 2016), against diabetes (Joseph et al, 2016), anti-inflammatory (El-Ahmady et al, 2013), anti-tumor, anti-cancer (Ashraf et al, 2016), for diabetes, vomiting, diarrhea and dyslipidemias (Elias et al, 2017) and leaves aqueous extracts of Psidium guajava use for obesity and dyslipidemias (Simao et al, 2017). These outcomes ratify high UV and RFC index of above stated medicinal plants in district Faisalabad.…”
Section: Use Value (Uv) and Relative Frequency Of Citation (Rfc)mentioning
confidence: 94%
“…Penggunaan daun jambu biji sebagai obat tradisional di Indonesia untuk berbagai macam penyakit seperti sariawan, batuk, diare, sembelit, luka, haid tidak lancar, kanker, maag, masuk angin, flu dan demam berdarah namun lebih dari itu dalam daun jambu biji diketahui mengandung pektin yaitu serat larut air yang berfungsi dapat menurunkan kadar kolesterol (Diana et al, 2021;Rahayu et al, 2016). Penelitian menggunakan ekstrak etanol P.guava secara signifikan dapat menurunkan tekanan darah (Elias et al, 2017). Hasil penelitian ini sejalan dengan beberapa penelitian terdahulu.…”
Section: Gambar 1 Perbandingan Perubahan Tekanan Darah (Mmhg) Pada Ti...unclassified
“…P.guajava juga memiliki anti diare dan aktivitas antimikroba (Ezekwesili et al, 2010). Efek menguntungkan pada P.guajava kemunkinan berkaitan dengan kandungan zat gizi dan zat nongizi seperti vitamin C, vitamin A, zat besi, kalsium, mangan, posfor, oksalat, dan asam malac, saponin kombinasi dengan oleanolic (Elias et al, 2017).…”
Section: Gambar 1 Perbandingan Perubahan Tekanan Darah (Mmhg) Pada Ti...unclassified
See 1 more Smart Citation